Use of habitat suitability model as a tool to highlight best conservation area for the red-bellied monkey (Cercopithecus erythrogaster erythrogaster) in Southern-Benin, West Africa. - ZOFFOUN, Omobayo Ghislain; NOBIME, GEORGES; SINSIN, AUGUSTIN BRICE; LINSOUSSI, AGOSSA CÔME (My University, 2022)
Wildlife habitats are increasingly degraded as a result of anthropogenic pressures. The IUCN recently updated the red list category of the red-bellied monkey (Cercopithecus erythrogaster erythrogaster) from Endangered to Critically Endangered due to its population decrease, habitats degradation and various threats to its conservation. It is therefore important to identify areas of great importance for the sustainable conservation of the subspecies. The Species Distribution Model (SDM) is a method increasingly used by conservationists to help find these areas and thus limit areas of intervention. In this study, maximum entropy model was used to identify suitable habitats for the red-bellied monkey in landscape of southern-Benin from occurrence data and selected predictor variables according to ecological habitat requirements of the subspecies. The suitable habitat model for the red-bellied monkey has a good predictive power (AUC = 0.97). The variables that contributed most to the final model, as indicated by the permutation importance, were: Distance to Water (47.7%), Land Cover Class (23.1%), Brightness (17.0%), Wetness (4.7%), Human Population Size (2.8%) and Elevation (2.2%). Thus, using Maximum Training sensitivity and Specificity threshold, 3.62% of the landscape was classified as suitable and 96.38% was classified as unsuitable for the red-bellied monkey. The largest area of suitable habitat is found in protected areas (57.46%), mainly in the Lama Forest Reserve central core (49.5%). The landscape is fragmented and 91.49% of suitable habitats are between 0 and 0.01 km2 in size. The mean size of suitable habitats in the landscape is 0.017 ± 0.545 km2. Nevertheless, there is no significant difference between the mean size of suitable habitats in protected areas and those in the unprotected area (P = 0.061, Mann-Whitney U tests). The Average Nearest Neighbor Distance of suitable habitats in the landscape is low (0.139 km) and the Average Nearest Neighbor Ratio (R) is less than 1 (R = 0.408, p < 0.001). Those features indicate a clustered pattern of suitable habitats for the red-bellied monkey in the landscape. This makes it possible to foresee the establishment of connections between the isolated suitable habitats and thus allow for the long-term conservation of the species populations.
Keywords: Red-bellied monkey; Species Distribution Model; Suitable habitat; Protected areas; Anthropogenic pressures